2010
DOI: 10.1111/j.1600-0714.2009.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

FAS and ErbB2 expression in early local recurrent oral cancer

Abstract: Histopathological characteristics and the expression of FAS and ErbB2 carry prognosis importance in local recurrence and overall survival in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
2
9
0
8
Order By: Relevance
“…Higher values failed to present many of these associations. PINTO et al 23 have also reported the same value as a better cutoff point for the Anneroth system, which was also related to survival rates (OS and DFS). In the same way, the Bryne score was classified according to the median value (10) and higher values until 12 points were attained.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 81%
See 2 more Smart Citations
“…Higher values failed to present many of these associations. PINTO et al 23 have also reported the same value as a better cutoff point for the Anneroth system, which was also related to survival rates (OS and DFS). In the same way, the Bryne score was classified according to the median value (10) and higher values until 12 points were attained.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 81%
“…Although biomarkers have been widely studied to better evaluate prognosis in oral cancer 8,14,16,19,23,28,33,36 , there is no routine clinical application of them. Some studies have presented controversial results regarding the same biomarkers 8,16 , compromising the universal acceptance for evaluating prognosis.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario was also observed and reported in oral dysplastic premalignant disorder (Hou et al, 1992). Thus, it was suggested as a marker for oral cancer (Li et al, 1992;Xia et al, 1997;Werkmeister et al, 1999;Fong et al, 2008) and also as a prognostic marker (Pinto et al, 2010;Stoicanescu et al, 2013) for monitoring disease progression. However, there is also evidence stating that low/absence of HER2/neu expression in oral cancer (Khan et al, 2002;Schartinger et al, 2004;Henning Hanken et al, 2014).…”
Section: Discussionmentioning
confidence: 54%
“…Among those bioactive molecules are the cytokines, molecules involved at the immunomodu--lizing local tissue ASCs through environmental modulation. It means that, even if the graft of transplanted stem cells bioactive molecules that are able to accelerate the healing of injured site (Zhao et al, 2004;; Kamiya et al, 2005 Santos et al, 2008;; Pinto et al, 2009). In the mean time, the biggest advantage of iPSCs is the fact they can be originated from any cell of the body as, for example, dermal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%